Orographically induced spontaneous imbalance within the jet causing a large-scale gravity wave event - Geldenhuys, Markus; Preusse, Peter; Krisch, Isabell; Zülicke, Christoph; Ungermann, Jörn; Ern, Manfred; Friedl-Vallon, Felix; Riese, Martin (Atmospheric Chemistry and Physics, 2021)
To better understand the impact of gravity waves (GWs) on the middle atmosphere in the current and future climate, it is essential to understand their excitation mechanisms and to quantify their basic properties. Here a new process for GW excitation by orography-jet interaction is discussed. In a case study, we identify the source of a GW observed over Greenland on 10 March 2016 during the POLSTRACC (POLar STRAtosphere in a Changing Climate) aircraft campaign. Measurements were taken with the Gimballed Limb Observer for Radiance Imaging of the Atmosphere (GLORIA) instrument deployed on the High Altitude Long Range (HALO) German research aircraft. The measured infrared limb radiances are converted into a 3D observational temperature field through the use of inverse modelling and limited-angle tomography. We observe GWs along a transect through Greenland where the GW packet covers ~1/3 of the Greenland mainland. GLORIA observations indicate GWs between 10 and 13km altitude with a horizontal wavelength of 330km, a vertical wavelength of 2km and a large temperature amplitude of 4.5K. Slanted phase fronts indicate intrinsic propagation against the wind, while the ground-based propagation is with the wind. The GWs are arrested below a critical layer above the tropospheric jet. Compared to its intrinsic horizontal group velocity (25 -- 72m/s) the GW packet has a slow vertical group velocity of 0.05 -- 0.2m/s. This causes the GW packet to propagate long distances while spreading over a large area while remaining constrained to a narrow vertical layer.Not only orography is a plausible source, but also out of balanced winds in a jet exit region and wind shear. To identify the GW source, 3D GLORIA observations are combined with a gravity wave raytracer, ERA5 reanalysis, and high-resolution numerical experiments. In a numerical experiment with a smoothed orography, GW activity is quite weak indicating that the GWs in the realistic orography experiment are due to orography. However, analysis shows that these GWs are not ...